Infantile juvenile polyposis syndrome: A rare cause of protein-losing enteropathy - Gülcü, Didem; Beser, Faruk; Kepil, Nuray; Erdamar, Sibel; Cullu, Fugen; Erkan, Tulay; Kutlu, Tufan (Journal of Surgery and Medicine, 2020)
Juvenile Polyposis Syndrome (JPS) is a rare autosomal dominant hereditary syndrome affecting 1:100000-160000 individuals. JPS most presents with rectal bleeding, anemia, abdominal pain, obstruction and rarely with rectal prolapsus of the polyp. In this case, we diagnosed Infantile Juvenile Polyposis Syndrome due to protein losing enteropathy, rectal bleeding and extraintestinal manifestations of the syndrome. A 2-year-old male infant was referred to the hospital due to complaints of painless rectal bleeding and rectal prolapsus of the polyp which occurred at 15 months of age. Pathological examination revealed that it was a juvenile polyp. After a short while, the patient was hospitalized due to rectal bleeding, paleness, swelling in both legs and periorbital edema. Physical examination of the patient revealed +3 pretibial, scrotal, periorbital edema, clubbing and pale appearance. The patient had macrocephaly, hypotonicity and neuromotor retardation. Laboratory test results revealed low immunoglobulin levels, hypoalbuminemia, anemia, and electrolyte imbalance. We diagnosed the case with JPS due to protein losing enteropathy with extraintestinal manifestations of the syndrome. Gastroscopic and colonoscopic examinations revealed multiple polyps through the antrum and colon. JPS diagnosis is based on the detection of polyps which are histopathologically defined as juvenile polyps. One of the most common causes of painless, rectal bleeding in children are colorectal polyps. We wanted to emphasize that the sporadic juvenile polyp diagnosis should be made by pathological examination of polypectomy material and clinical exclusion of JPS. In our patient, there were extraintestinal system manifestations such as macrocephaly, congenital heart disease and clubbing, accompanied with protein-losing enteropathy. Awareness of these clinical findings is necessary for the differential diagnosis of protein-losing enteropathy and polyposis syndrome. We would also like to draw attention to the importance of a multidisciplinary approach, early recognition of the syndrome and appropriate referral of the patient.